Research Trends of Computational Thinking: A Bibliometric Review Over Three Decades - Sela Marselyana Abadi (Scientia Publica Media, 2024)
Currently, computational thinking is considered one of the future abilities that students must have. However, existing research has not offered comprehensive findings and explorations of computational thinking. This research presents bibliometric analysis research to investigate the development of research on computational thinking abilities at all levels of education. Specifically, the main aim of this research is to analyze trends in computational thinking research using bibliometric mapping based on variables: publications, citations, keywords, journals, authors, and countries. The initial search produced 5188 documents, which were then filtered into 1599 articles according to the inclusion and exclusion criteria. The first article recorded was from 1987 and the number of articles published increased in 2014-2022. This shows that the research trend in computational thinking has become a quite popular research topic in line with the awareness of the importance of computational thinking skills as one of the abilities that must be needed by the current generation. In relation to keywords related to computational thinking, discussion of computational thinking abilities is no longer limited to computer science or programming, but has spread to education, whether learning, assessment, or other supporting abilities. In addition, it is also identified the most productive journals in producing research on this topic, along with institutions and countries that have made major contributions to the related research. As the most productive country, the United States leads the list, followed by China and Türkiye. Overall, these results provide a broad picture of understanding regarding the development of computational thinking abilities that have been connected to various fields. Therefore, in the field of education, it is appropriate for policy holders to consider computational thinking skills to be integrated into the current curriculum.